Planar wheel-type M©BnHn2−/−/0 clusters (M = Cr, Mn and Fe for dianion, anion and neutral, respectively; n = 6 and 7). Issue 49 (30th May 2015) - Hou, Jianhua; Duan, Qian; Qin, Jieming; Shen, Xiande; Zhao, Jianxun; Liang, Qingcheng; Jiang, Dayong; Gao, Shang
<x xml:space="preserve">Abstract</x> A new "electronic" strategy that adds two electrons into the dz2 orbital of the central M atom to form a lone pair, in contrast to Hoffmann's "electronic" strategy to turn the bowl-type MBnHn0/+ (M = Cr and Mn; n = 6 and 7) clusters into planar wheel-type clusters.